Review of Port Management Integrated Digitization System: A Pathway to Efficient and Sustainable Port Operations - Kusumawati , Evyana Diah; Karjono, Karjono; Karmanis, Karmanis (Maritime Park: Journal of Maritime Technology and Society, 2023)
The maritime industry has significantly contributed to the global economy, with ports as the primary international trade and transportation nodes. However, the increasing complexity of port operations, coupled with the growing demand for efficient and sustainable practices, has necessitated the adoption of innovative technologies. This essay explores the concept of the Port Management Integrated Digitization System (PMIDS) and its potential to revolutionize port operations. The discussion covers the various components of PMIDS, including the Internet of Things (IoT), big data analytics, artificial intelligence (AI), and blockchain technology. Furthermore, the essay delves into the benefits of implementing PMIDS, such as enhanced operational efficiency, improved safety and security, and reduced environmental impact. Finally, the challenges and prospects of PMIDS are examined, highlighting the need for a collaborative approach among stakeholders to ensure the successful implementation of this transformative technology.